A general asymmetric route to enantio-enriched isoflavanes via an organocatalytic annulation of o-quinone methides and aldehydes. Issue 25 (20th June 2018) - Zhang, Jian; Zhang, Shuangzhan; Yang, Huixin; Zhou, Ding; Yu, Xueting; Wang, Wei; Xie, Hexin
Graphical abstract: Highlights: A general asymmetric route to isoflavanes was developed. Five optically active natural isoflavanes were prepared. High synthetic efficiency. Abstract: Reported herein is a general approach to optically active isoflavanes based on a chiral amine-catalyzed [4 + 2] asymmetric annulation of o -quinone methides and aldehydes. A number of naturally occurring isoflavanes, including equol, sativan, isosativan, vestitol and medicarpin, as well as isoflavane analogues were readily prepared with good to excellent enantioselectivities.